Pengaruh Forgiveness terhadap Subjective Well-Being pada Perempuan Yang Mengalami Kekerasan dalam Berpacaran - Rafika Kharisma Firdhausy; Maria Goretti Adiyanti (Universitas Muhammadiyah Metro, 2026)
This study aims to examine the effect of forgiveness on subjective well-being among women who experience dating violence. A quantitative method was applied in this research. The participants were women aged 18–25 years living in Java Island who were currently experiencing or had previously experienced violence in dating relationships, selected using incidental sampling. Data were collected using the Satisfaction with Life Scale (SWLS) and the Positive Affect and Negative Affect Scales (PANAS) to measure subjective well-being, and the Transgression-Related Interpersonal Motivations (TRIM) Inventory-18 to assess forgiveness. Data analysis was conducted using simple linear regression. The results indicate that forgiveness has a positive and significant effect on subjective well-being (p < 0.05), with a contribution of 21.5%. These findings show that forgiveness plays an important role in supporting the psychological well-being of women who experience dating violence. This study is expected to contribute to the development of positive psychology and provide practical implications for psychological recovery efforts among female survivors of dating violence.